(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
In this article are presented some materials from a domus in the residential area of Nora, still under excavation. Numerous fragments of plaster have been found inside the room A of the Casa del Pozzo (CdP), inside a filling of building materials. Among these are some fragments of painted plaster, a fragment of plaster with inscription on and a fragment of cornice.